Modulation of plant development and chilling stress responses by alternative splicing events under control of the spliceosome protein SmEb in Arabidopsis. (12th July 2022) - Wang, Zhen; Hong, Yechun; Yao, Juanjuan; Huang, Huan; Qian, Bilian; Liu, Xue; Chen, Yunjuan; Pang, Jia; Zhan, Xiangqiang; Zhu, Jian‐Kang; Zhu, Jianhua
Abstract: Cold stress resulting from chilling and freezing temperatures substantially inhibits plant growth and reduces crop production worldwide. Tremendous research efforts have been focused on elucidating the molecular mechanisms of freezing tolerance in plants. However, little is known about the molecular nature of chilling stress responses in plants. Here we found that two allelic mutants in a spliceosome component gene SmEb ( smeb‐1 and smeb‐2 ) are defective in development and responses to chilling stress. RNA‐seq analysis revealed that SmEb controls the splicing of many pre‐messenger RNAs (mRNAs) under chilling stress. Our results suggest that SmEb is important to maintain proper ratio of the two COP1 splicing variants ( COP1a / COP1b ) to fine tune the level of HY5. In addition, the transcription factor BES1 shows a dramatic defect in pre‐mRNA splicing in the smeb mutants. Ectopic expression of the two BES1 splicing variants enhances the chilling sensitivity of the smeb‐1 mutant. Furthermore, biochemical and genetic analysis showed that CBFs act as negative upstream regulators of SmEb by directly suppressing its transcription. Together, our results demonstrate that proper alternative splicing of pre‐mRNAs controlled by the spliceosome component SmEb is critical for plant development and chilling stress responses. Abstract : We performed a forward genetic analysis for critical molecular components in plant chilling stress responses. The spliceosome component SmEb plays an essential role in plant development and chilling stress responses, providing valuable information for improvement of cold tolerance in plants.